PERAN JOB CRAFTING MENINGKATKAN JOB PERFORMANCE PADA KARYAWAN PENJUALAN - Dewi, Rina (STIE Mahardhika, 2025)
Job crafting is a proactive process by employees in work tasks so that work has significance and is more meaningful based on individual belief values that influence job performance. This research aims to examine and analyze the role of job crafting which consists of task crafting, relational crafting and cognitive crafting in improving job performance in the context of sales employees. The object of this research focuses on sales employees who have an important role for the success of every business. Sales employees often face various challenges that can affect their team's performance and overall sales results. This research uses a quantitative method with three proposed research hypotheses which will then be analyzed and tested to answer the research problems. Data analysis techniques using multiple linear regression to produce good prediction results in providing research result reports. This research uses 298 research samples of sales employees from various industries in Surabaya. The findings of the three hypotheses were all accepted. Task crafting for sales employees has the most dominant influence on job performance. The company's research contribution must provide opportunities for sales employees to carry out job crafting to improve job performance. Task crafting contributes to building employees to understand their work more meaningfully which leads to improved job performance in sales employees. Relational crafting can improve quality business relationships in interactions between individuals in the organization at work which encourages increased job performance. While cognitive crafting contributes to building job alignment by connecting personal ideals and desires with work goals.